2021
DOI: 10.1002/ijop.12761
|View full text |Cite
|
Sign up to set email alerts
|

Being an accountant, cook, entertainer and teacher—all at the same time: Changes in employees' work and work‐related well‐being during the coronavirus (COVID‐19) pandemic

Abstract: I n March 2020, the world was hit by the coronavirus disease (COVID-19) pandemic which led to all-embracing measures to contain its spread. Most employees were forced to work from home and take care of their children because schools and daycares were closed. We present data from a research project in a large multinational organisation in the Netherlands with monthly quantitative measurements from January to May 2020 (N = 253-516), enriched with qualitative data from participants' comments before and after tele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
109
3
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(122 citation statements)
references
References 39 publications
7
109
3
3
Order By: Relevance
“…For example, a longitudinal study conducted between September 2019 and April 2020 (Möhring et al, 2021) found an overall decline in work satisfaction because of the first national lockdown in Germany, particularly among working mothers and among childless employees who had to switch to shorttime work. Another study conducted between January and May 2020 (Syrek et al, 2021) found general decreases in work engagement, increases in job satisfaction as well as initial declines in work-nonwork balance, workload, and autonomy need satisfaction, followed by recovery patterns in May 2020. Finally, a study conducted between April and June 2020 (Meyer et al, 2021) showed that female employees with low partner support experienced higher levels of exhaustion during the lockdown in Germany.…”
Section: Declines In Self-reported Work Performance Because Of the Lockdownmentioning
confidence: 99%
“…For example, a longitudinal study conducted between September 2019 and April 2020 (Möhring et al, 2021) found an overall decline in work satisfaction because of the first national lockdown in Germany, particularly among working mothers and among childless employees who had to switch to shorttime work. Another study conducted between January and May 2020 (Syrek et al, 2021) found general decreases in work engagement, increases in job satisfaction as well as initial declines in work-nonwork balance, workload, and autonomy need satisfaction, followed by recovery patterns in May 2020. Finally, a study conducted between April and June 2020 (Meyer et al, 2021) showed that female employees with low partner support experienced higher levels of exhaustion during the lockdown in Germany.…”
Section: Declines In Self-reported Work Performance Because Of the Lockdownmentioning
confidence: 99%
“…The uniqueness of the situation also changed the provision of education on a global level [39]. Research shows that employees attempted to fill different roles, create new procedures, and control work-life balance [40]. Issues like poor work conditions, difficulties with students and families, and other problems with work organization became clear as factors limiting the success of telework [39].…”
Section: Education Professionals' Challenges With Telework During the Pandemicmentioning
confidence: 99%
“…Neuropsychological disorders are influenced by the mandatory additional effort required to organize education activities [43]. It is important to note that women's mental health has been harmed more due to the COVID-19 restrictions than men's [40]. Bearing in mind the fact that there are more female teachers, it can be forecast that the education sector might be faced with future challenges related to teacher burnout and withdrawal due to fatigue.…”
Section: Education Professionals' Challenges With Telework During the Pandemicmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, a longitudinal study conducted between September 2019 and April 2020 found an overall decline in work satisfaction due to the first national lockdown in Germany, particularly among working mothers and among childless employees who had to switch to short-time work (Möhring et al, 2021). Another study conducted between January and May 2020 found general decreases in work engagement, increases in job satisfaction, as well as initial declines in work-nonwork balance, workload, and autonomy need satisfaction, followed by recovery patterns in May 2020 (Syrek et al, 2021).…”
Section: Declines In Self-reported Work Performance Due To the Lockdownmentioning
confidence: 99%